2021
DOI: 10.1024/1016-264x/a000336
|View full text |Cite
|
Sign up to set email alerts
|

Die Erhebung von kommunikativ-pragmatischen Fähigkeiten und Lebensqualität nach Schädel-Hirn-Trauma

Abstract: Zusammenfassung. Hintergrund: Kommunikationsstörungen nach Schädel-Hirn-Trauma (SHT) können die Betroffenen langfristig in der sozialen Teilhabe und damit in der Lebensqualität (LQ) beeinträchtigen. Der Erfassung dieser Störungen liegt aktuell kein einheitliches Vorgehen zugrunde. Ziele: Ziel des vorliegenden Scoping Reviews war die Erfassung von Diagnostikverfahren, welche die kommunikativ-pragmatischen Kompetenzen und die Auswirkung möglicher kommunikativer Defizite auf soziale Teilhabe und LQ bei Menschen m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…The search strategy was performed on the title, the publication date of the literature was restricted from 2010-01-31 to 2023-01-31. We chose a time period comparable to a previous scoping review by this group of authors (Falkowska et al, 2021), covering the period from 2010 to 2023. Depending on the database, the results were either filtered by adulthood or filtered manually according to the age group.…”
Section: Search Strategymentioning
confidence: 99%
“…The search strategy was performed on the title, the publication date of the literature was restricted from 2010-01-31 to 2023-01-31. We chose a time period comparable to a previous scoping review by this group of authors (Falkowska et al, 2021), covering the period from 2010 to 2023. Depending on the database, the results were either filtered by adulthood or filtered manually according to the age group.…”
Section: Search Strategymentioning
confidence: 99%
“…Various reviews highlight that the consequences of severe TBI can have a negative impact on social and occupational participation as well as on the individual quality of life (Ponsford et al, 2014;Schwenkreis, 2018;Neumann et al, 2019;Falkowska et al, 2021). The massive impact of discourse disorders on social participation has long remained unrecognized, even though individuals directly affected by TBI, as well as their caretakers and relatives, have been highly aware of the negative influence of discourse disorders on their daily lives (Ponsford et al, 2014;Falkowska et al, 2021). Factors influencing participation deficits include impairments in social cognition (Milders, 2019), EFs (Douglas, 2010a), and communication deficits ( Douglas et al, 2007a).…”
Section: Assessing Discourse In Traumatic Brain Injury: Insights Into...mentioning
confidence: 99%
“…The LCQ is currently the only standardized questionnaire in German-speaking countries that can be used to assess sociocommunicative impairment and resources after TBI from the perspective of the affected person (self-assessment) and a close person (Büttner-Kunert et al, 2021b;Falkowska et al, 2021). In evaluation studies on the LCQ, neurologically healthy persons showed a significantly more critical self-assessment (LCQ-S) compared to the assessment of close others (LCQ-O), regardless of sex and educational level (Büttner-Kunert et al, 2021a).…”
Section: Assessing Discourse In Traumatic Brain Injury: Insights Into...mentioning
confidence: 99%
“…PmD empfinden ihre Einschränkungen daher anders und bewerten sie emotional anders als Angehörige/Bezugspersonen oder Fachpersonal 39 . Daher ist für neurologisch bedingte Kommunikationsstörungen generell ein multiperspektivischer Zugang zu empfehlen, bei dem unterschiedliche Einschätzungen sich ergänzen und zu einem Gesamteindruck beitragen 40 41 .…”
Section: Limitationenunclassified